PENGARUH FINANCIAL DISTRESS DAN AUDIT DELAY TERHADAP AUDITOR SWITCHING (Studi Kasus pada Perusahaan Sub Sektor Maknanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2013 – 2017) - Pratiwi, Maharani Putri; Rispantyo, Rispantyo; Harimurti, Fadjar (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
The purpose of this study aims to find empirical evidence about the factors that influence auditor switching in food and beverage sub-sector companies listed on the Indonesia Stock Exchange. The factors tested in this study are financial distress and audit delay. The sample in this study used 14 food and beverage sub-sector companies listed on the Indonesia Stock Exchange in the period 2013 - 2017 taken using the Purposive Sampling method. These factors are then tested by logistic regression at a significance level of 5 percent. The results of the study identified that financial distress did not have a significant negative effect on auditor switching, while audit delay had a significant positive effect on auditor switching in the food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2013 - 2017.